Evaluasi Sensori, Nilai Gizi, dan Sifat Fisik Cookies Kedelai Hitam untuk Ibu Menyusui - Rianita Pramitasari; Gracia Halim; Vivitri Dewi Prasasty (Universitas Muhammadiyah Semarang, 2017)
The purpose of this study was to get sensory attributes and determine the nutrient composition and physical property of black soybean cookies for breastfeeding mothers. Cookies were made from 5 ratio variations of wheat flour : black soybean flour with baking temperature 1350C for 30 minutes. Further analysis of sensory (taste, flavor, color, texture, aftertaste, and overall; physical property (hardness); and chemical analysis (moisture, protein, lipid, ash, and carbohydrate) to determine the nutritional composition. The results showed that the cookies with ratio wheat flour : black soybean 75:25 was the most preferred cookies by panelists. One cookies contained 3.17 grams of carbohydrate; 0.62 grams of protei; and 1.62 grams of lipid. It could suffice 1.12% of total energy based on Recommended Dietary Allowance of breastfeeding mother per day. The level of hardness was 21.90 N, higher than the control cookies without black soybean flour. Key words : cookies, black soybean, breasfeeding mother.